Development of a Standard Curve to Account for Viable Loads of Bifidobacterium animalis subsp. lactis HN019 Using RNA by Real-Time PCR. (23rd November 2019) - Ali, Md. A; Hui, Wang; Lin, Guangen; Dang, Fang F; Wu, Shuang; Man, Chaoxin; Jiang, Yujun
Abstract: Background: Bifidobacterium animalis subsp. lactis HN019 is widely used as a probiotic in various dairy preparations. To ensure optimal health benefits, an adequate number of probiotics should be viable in products, but the culture-based methods require longer periods to account for the strain. Objective: Develop a standard curve to account viable loadof B. animalis subsp. lactis HN019 by real-time PCR. Methods: The growth curve was developed accordingto plate count method, and cycle threshold (CT ) curve was prepared using CT values. These two curves were then combined to construct the standard curve. To validate the method, the strain was proliferated in whole milk, and viable loads were enumerated by plate counting and relativePCR counting followed by determining the SEM betweenthe two counts. Results: The growth curve and CT curve, respectively, showed the highest viable load (2.13 × 10 8 CFU/mL) and lowest CT value (18.29) after 18 h, and during the entire growth phase (0–18 h), viable loads are inversely proportional to the CT values. The standard curverevealed the model y = 2E + 18e −1.233 x ( y = cells/mL, x = CT value; R 2 = 0.992). In validation, the highest SEM (± 0.70 × 10 8 ) was found between the plate count (1.15 × 10 8 cells/mL) and relative PCR count (1.29 × 10 8 cells/mL) after cultivating for 14 h. Conclusions: The method could be readilyused in dairy industries to quantify viable B. animalis subsp. lactis HN019 by a shorter period. Highlights: Culture-independent enumeration of viable B. animalis subsp. lactis HN019 by real-time PCR.